Influence of End Milling Process Variables on Material Removal Rate and Surface Roughness of Direct Metal Laser Sintered Inconel 718 Plate. (25th September 2022) - Parthasarathi, N. L.; Veeman, Dhinakaran; Dhamodharan, Duraisami; Borah, Utpal; Ravichandran, M.; Natrayan, L.; Degife Mammo, Wubishet
Abstract : This study intends to optimize the end milling process variables for additively manufactured (AM) Inconel 718 alloy through the direct metal laser sintered (DMLS) method. Surface roughness and material removal rate have been considered as output responses. The end milling experiments were conducted using the design of experiments with an L 9 orthogonal array (OA) by varying the process variables like feed rate (mm/min), cutting speed (m/min), and depth of cut (mm). Taguchi technique was used to optimize the process variables. Examination of the variance table is working to regulate each variable's percentage contribution and significance in end milling experiments. The chip morphology of the DMLS Inconel 718 plate reveals that, at lower cutting speed, irregular and discontinuous chips were formed.